Soccer standing throw-in performance : effects of learning with weighted ball - Krishnasamy, Bhanu (Nanyang Technological University, 2020)
Purpose: To determine if learning with different weighted balls could cause any effect on women soccer players’ standing throw-in horizontal distance, accuracy and technique (ball release angle and ball release speed). Method: Twelve university women soccer players from Nanyang Technological University (NTU) were randomly grouped into three different training groups (soccer ball, medicine ball and combination of both soccer ball and medicine ball) with the same workload across all groups. All participants underwent a pre-test, eight training sessions (twice per week) over four weeks and a post-test. Players’ throw-in maximum horizontal distance and technique were measured from video using Kinovea while players’ accuracy was observed by the author. Results: A significant increase (p < 0.05) was found in all participants’ throw-in horizontal distance and ball release speed only. In contrast, no significant difference was found in the participants’ throw-in accuracy and ball release angle. There was no group interaction found between any training groups for all variables tested. Conclusion: Practicing with different weighted balls proved to improve NTU women soccer players’ standing throw-in horizontal distance and ball release speed but not accuracy and ball release angle.